Adoption of renewable home heating systems: An agent-based model of heat pump systems in Ireland - Tensay Hadush Meles; Lisa Ryan (University College Dublin, UCD Centre for Economic Research, 2020)
Concern about climate change and dependence on fossil fuels is inducing countries to develop and deploy renewable energy technologies. Heat pump systems, which extract heat either from the air, water, or ground sources, are among the viable options for space heating and domestic hot water production in the residential sector. In this paper, we develop an agent-based model to analyze the adoption process of heat pump systems and the underlying diffusion factors. Uniquely, we use a recent nationally representative Irish household survey data to derive parameters for decision rules for technology adoption in the model. In this research, we explore how financial aspects, psychological factors and social networks influence the adoption and diffusion of heat pump systems. We also discuss how individual household socio-demographic characteristics, building characteristics, geographical location of household and policy incentives affect the adoption process. The research should be of interest to policymakers, as we use the model to test the impact of various policies on technology adoption rates.
Keywords: D12; D91; Q41; Q68; Q28; 330; Agent-based model; heat pump systems; energy economics; renewable energy technology adoption; Ireland